Preparation of Processed Cheese - Novita Dewi (Faculty of Animal Science Universitas Brawijaya, 2007)
This research was carried out to study the effects of kinds of enzyme and emulsifier on pH value, titratable acidity, water content, protein, fat and texture (objective and organoleptic tests) of processed cheese.Â The kinds of emulsifier effected pH value and titratable acidity, and interaction between the kinds of emulsifier and enzyme affected texture (objective and organoleptic tests) and general acceptance.Â Kind of emulsifier affected protein content andÂ texture (organoleptic test) of processed cheese. Keywords : cheese, enzyme, emulsifier